1971
DOI: 10.1051/jphyscol:1971444
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption of Solid Neon and Argon in the Soft X-Ray Region

Abstract: The absorption spectra of thin films of solid Ne and Ar have been measured in the photon energy range 25 to 500 eV. For comparison with the atomic states the corresponding spectra in the gas have also been investigated. The 7.5 GeV electron synchroton DESY served as light source. Near the onset of inner shell transitions (2 s in Ne, 3 s and 2 p in Ar) fine structure can be seen which is characteristic for the solid or atomic state. The structure in the spectra of the solid is ascribed to exciton and interband … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Small blue-shifts of 4 . 3 5 eV are observed for surface excitons, whereas bulk core excitons are blue-shifted by = l eV, as observed for the solid (20). For large clusters (N=530) the maximum of the lowest exciton state at 244.8 eV shows a shift which is typical for surface excitons, contrary to total electron yield and ZEKE yields recorded under identical expansion conditions where the contribution of bulk excitons dominates (4,17).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Small blue-shifts of 4 . 3 5 eV are observed for surface excitons, whereas bulk core excitons are blue-shifted by = l eV, as observed for the solid (20). For large clusters (N=530) the maximum of the lowest exciton state at 244.8 eV shows a shift which is typical for surface excitons, contrary to total electron yield and ZEKE yields recorded under identical expansion conditions where the contribution of bulk excitons dominates (4,17).…”
Section: Resultsmentioning
confidence: 57%
“…This is especially true for the lowest Ar(2p),,+4s transition, since it is an isolated Frenkel-type exciton (20). Small blue-shifts of 4 .…”
Section: Resultsmentioning
confidence: 97%
“…It has been found that the shapes of inner shell absorption spectra of isolated atoms differ from those of the corresponding condensed species. 3 In contrast to this valence transitions of core excited molecular species (1s→π*) show typically the same energy positions in the gas and condensed phase. 4 However, intensity changes of discrete resonances relative to the corresponding ionization continua are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 2b for a two body dissociation reaction (Ar 3 ++ →Ar + /Ar 2 + ). Various other charge separation reactions involving three body dissociations and evaporation of neutrals are discussed in ref.…”
Section: Atomic Clustersmentioning
confidence: 99%
See 1 more Smart Citation